Bcl‐2 is required for the survival of doublecortin‐expressing immature neurons. Issue 2 (17th September 2015) - Ceizar, Maheen; Dhaliwal, Jagroop; Xi, Yanwei; Smallwood, Megan; Kumar, Keren Leviel; Lagace, Diane C.
ABSTRACT: In the adult brain only a small proportion of the neural stem and progenitor cells (NPCs) and their progeny survive to become mature neurons in the hippocampus. Recent studies have elucidated the roles for members of the B‐cell lymphoma‐2 (Bcl‐2) family of proteins in regulating the survival of NPCs and their progeny at different stages of maturation, yet the requirement of Bcl‐2 during this process remains unknown. Here we report that inducible removal of Bcl‐2 from nestin‐expressing neural stem/progenitor cells and their progeny resulted in a reduction in the survival of doublecortin‐expressing cells in the absence of changing the number of radial‐glial stem cells or dividing NPCs. The requirement of Bcl‐2 for the survival of maturing NPCs was confirmed by removal of Bcl‐2 through infecting NPCs using a retroviral strategy that resulted in the complete loss of Bcl‐2 null cells by 30‐day post‐viral injection. Furthermore, we observed that the function of Bcl‐2 in the adult‐generated neurons was dependent on the Bcl‐2‐associated X (BAX) protein, since Bcl‐2 null NPCs were rescued in BAX knockout mice. These results indicate that Bcl‐2 is an essential regulator in the survival of doublecortin‐expressing immature neurons through a mechanism that is upstream of BAX. © 2015 Wiley Periodicals, Inc.